Strategi Perencanaan Pengembangan Sistem Sap pada Human Capital and Legal di Institusi Pendidikan Xyz - Evy Ekawati (Bina Nusantara University, 2014)
The increasing complexity of processes and operational functions cause arises the need for an integrated information system across all functional areas to reach the highest point of effectiveness and efficiency, and relying on the information in making decisions, ie ERP (Enterprise Resource Planning). The objective of writing this journal is to analyze and determine a SAP system development strategy planning at Human Capital and Legal of Education Institution XYZ. In collecting data, the author collected the datas by making an interview with the sources, data observation, and SAP system exploration. Current architecture datas that were collected and anylized to design the planning strategy in developing system architecture. The conclusion of this journal writing is that planning with some methodologies could maximize the using of IS or IT in an organization and can achieve its goals.